THE INFLUENCE OF COMPANY IMAGE, PREMIUM PRICES AND PRODUCTS ON PEOPLE'S INTEREST IN CHOOSING SHARIA LIFE INSURANCE IN PALEMBANG CITY - Yolanda Adista Septiani Aksa; Ulil Amri; M. Iqbal (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Company image, premium prices and products are important factors and are the goals of every company, including those in the insurance sector. Apart from being an important factor as the front guard for the continuity of the company's operation, the existence of this factor can support the increase in public interest in insurance, especially sharia life insurance in the city of Palembang. The research conducted aims to determine the influence of company image, premium prices and products on people's interest in choosing sharia life insurance in the city of Palembang, focusing on sharia life insurance customers in the city of Palembang who are or have been sharia life insurance customers in the city of Palembang as the population. . The method used in collecting data is through a questionnaire using a Likert scale. Through the characteristics of sharia insurance users with a period of less than 1 year to more than 5 years and customers who are no longer customers. The sample consisted of 120 respondents using purposive sampling technique. Path Coefficient shows that Company and Product Image have a positive and significant influence on people's interest. Meanwhile, the premium price has no positive and significant effect on people's interest in choosing sharia insurance in the city of Palembang.